Will’s Story: Managing Culturally Irreconcilable Identities in Everyday Life - Fannon, Tara A. (Disability Studies Quarterly, 2020)
This paper presents a case analysis from a larger research project surfacing visually disabled men's experiences of masculinity and disability in everyday life. Using the Listening Guide, a voice-centered relational method of narrative analysis, and the work of Erving Goffman and Critical Disability Studies, I present Will's story of self-exploration and illuminate how he navigates and negotiates relationships and social life in American culture, where masculinity and disability are commonly constructed as irreconcilable statuses. This paper advances knowledge about the mutuality between identities and social-structural experiences, with impairment situated between these processes as an embodied tether, that gives meaning and provides nuance to one's understanding and experience of himself in the world as a visually disabled man.